Clinical epidemiological profile of the temporomandibular joint disorder in mexican patients with malocclusion - Moreno Rojas, Mayra Hortensia (Revista Mexicana de Ortodoncia, 2016)
The present article describes an epidemiological study of the prevalence of signs and symptoms of the temporomandibular joint disorder (TMJ) in 284 patients with malocclusion, first received in the Orthodontics Clinic of the Postgraduate Studies and Research Division (DEPeI) of the National Autonomous University of Mexico (UNAM). The aim was to determine the prevalence of signs and symptoms of temporomandibular joint disorder in a sample of patients aged 12 to 68 years with malocclusion prior to orthodontic treatment and occlusal, skeletal and demographic variables. Among the results, it was found that one third of the sample had some sign or symptom of Temporomandibular Disorder, and there was no statistically significant difference between men and women. One out of three patients for both Class III and Class II presented some sign or symptom of TMD. Forty-two percent of the cases with open bite, and thirty two percent with cross bite had TMD. One out of four cases with TMD presented pain in the masticatory muscles. Key words: Temporomandibular joint disorder, mexican population.